SYMMETRY AND CRYSTAL STRUCTURE OF BIAXIAL ELBAITE-LIDDICOATITE TOURMALINE FROM THE TRANSBAIKALIA REGION, RUSSIA - Shtukenberg A.; Rozhdestvenskaya I.; Frank-Kamenetskaya O.; Bronzova J.; Bannova I.; Euler H.; Kirfel A.; Zolotarev A. (My University, 2007)
Optical anomalies and crystal structures have been studied for an elbaite-liddicoatite tourmaline specimen from the Malkhan pegmatite field (Transbaikalia region, Russia). The specimen is characterized by a complicated zoning and sector zoning distribution of anomalous biaxiality, with the axial angle 2V increasing from 3 up to 23° going from the first to the last growth zones of the most developed growth sector, o{022̅1}. The crystal structures of three samples cut out from different growth zones of that sector and characterized by the axial angles 11, 16, and 23° were refined in the trigonal space group R3m as well as in its monoclinic and triclinic subgroups Cm, R1, and P1, respectively (R = 0.019–0.039). The final choice of the low symmetry space group R1 is based on the analysis of the diffraction patterns and on the results of crystal structures refinements, which revealed ordered Al/Li distributions over the Y octahedral sites. The degree of order at Y sites correlates with the axial angle 2V, which implies a causal relationship. The Al/Li ordering reflects the geometrical differences of the octahedral sites with respect to the growth front orientation. The results obtained suggest that a growth dissymmetrization mechanism is the main reason for the observed cation ordering and optical anomalies.
Keywords: DISSYMMETRIZATION; ELBAITE; GROWTH ORDERING OF ATOMS; LIDDICOATITE; OPTICAL ANOMALIES; TOURMALINE CRYSTAL STRUCTURE